Method for conducting alkali metal regulation and control doping in flexible copper-zinc-tin-sulfur-selenium battery
By inverted deposition of copper, zinc, tin, sulfur precursor films to perform selenization annealing on soda-lime glass coated with Mo layer, the problem of alkali metal doping control in flexible copper, zinc, tin, selenium solar cells is solved, the photoelectric conversion efficiency is improved and the Device performance.
Patent Information
- Application Number
- CN202411349211.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to effectively control alkali metal doping in flexible copper, zinc, tin, sulfur and selenium solar cells, resulting in excessive doping causing damage to the device and low conversion efficiency.
By inverting the copper-zinc-tin-sulphur precursor film onto the soda-lime glass plated with Mo layer for selenization annealing, alkali metal doping is achieved by diffusion of alkali metal in the soda-lime glass, and selenization annealing is performed in a nitrogen atmosphere. Control the distribution and content of alkali metals.
The regulation and doping of alkali metals in flexible copper, zinc, tin and selenium films is achieved, which significantly improves the photoelectric conversion efficiency of flexible CZTSSe solar cells, avoids the damage to the device by excessive alkali metal doping, and improves device performance.
Smart Images

Figure CN119208447A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to an alkali metal doping method in a flexible copper-zinc-tin-sulfur-selenium cell. Background Art
[0002] With the increasing economic development and energy shortage, the world's demand for energy is growing, and solar cells have received much attention. Copper zinc tin sulfur selenide (CZTSSe) is developed from copper indium gallium selenide. Similar to copper indium gallium selenide (CIGS), CZTSSe is also a direct bandgap semiconductor material. The Shockley-Queisser limit of the photoelectric conversion efficiency of a single-layer CZTSSe cell is as high as 32.2%. Its bandgap can be continuously adjusted between 1.0 and 1.5 electron volts, which can be well matched with the range of incident solar radiation. It has a high absorption coefficient, so in fact only a few microns of material are needed to absorb all sunlight. As the absorption layer of a photovoltaic cell, CZTSSe has a thickness of between 1 and 3 microns, which can produce low-cost, large-area, and high-efficiency photovoltaic cells. The material contains rich elements, is low-priced, and is harmless to the environment, so it has received widespread attention in recent years.
[0003] Compared with rigid soda-lime glass (SLG) substrates, solar cells based on flexible substrates are more attractive due to their low cost, light weight and convenient transportation. In addition, flexible solar cells can also be widely used in emerging fields such as wearable electronic devices, building integrated photovoltaics (BIPV), aerospace, etc. For copper-based solar cells, a variety of flexible substrates can be selected, such as Mo foil, polymer (PI), Ti foil, stainless steel (SS), flexible glass, etc. In recent years, the conversion efficiency of flexible CZTSSe solar cells has exceeded 12%, however, this is still a large gap with solar cells based on soda-lime glass.
[0004] It was first discovered in copper indium gallium selenide solar cells that the introduction of alkali metal elements can significantly improve the performance of solar cells, mainly through soda lime glass (SLG) as a substrate, because the alkali metal elements in soda lime glass will diffuse from SLG into the semiconductor film during high-temperature annealing, realizing a spontaneous alkali metal doping process. Alkali metal doping is also crucial for high-efficiency CZTSSe solar cells. It is generally believed that alkali metal doping can promote thin film crystal growth, increase the P-type conductivity of the material, and passivate defects. However, almost all flexible substrates lack alkali metal sources. Therefore, although the specific mechanism of alkali metal doping is still controversial, it has become a consensus that alkali metal doping is a key issue in realizing high-efficiency flexible CZTSSe solar cells.
[0005] Many studies on flexible CZTSSe solar cells are based on alkali metal doping. In vacuum processes, alkali metals are usually introduced by sputtering or evaporation. For non-vacuum processes, alkali sources are generally introduced into the CZTS precursor solution to achieve alkali metal doping. Unfortunately, it is difficult to control the distribution of alkali metal elements and the content of alkali metals in the film when doping flexible devices using the above traditional alkali metal doping methods. However, many studies have shown that excessive alkali metal doping can be harmful to the device. Therefore, finding a simple and controllable alkali metal doping method is crucial to effectively improve device performance. Summary of the invention
[0006] The present invention focuses on improving the conversion efficiency of flexible CZTSSe solar cells and provides a method for regulating alkali metal doping in flexible copper-zinc-tin-sulfur-selenium cells. The method provides a good basis for preparing high-efficiency flexible copper-zinc-tin-sulfur-selenium thin-film solar cells and can achieve a simple and effective improvement in the photoelectric conversion efficiency of flexible solar cells.
[0007] The above-mentioned object of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for regulating alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery, comprising the following steps:
[0009] S1: Deposition of copper-zinc-tin-sulfur precursor thin films on flexible substrates;
[0010] S2: placing the copper-zinc-tin-sulfur precursor film deposited on the flexible substrate upside down on Mo glass for selenization annealing, wherein the Mo glass is soda-lime glass coated with a Mo layer; the selenization annealing can achieve diffusion of alkali metals in the soda-lime glass and doping them into the copper-zinc-tin-sulfur-selenium film, wherein the alkali metals include sodium and potassium elements;
[0011] S3: A flexible copper-zinc-tin-sulfur-selenium battery is prepared based on a copper-zinc-tin-sulfur-selenium film doped with alkali metals.
[0012] Furthermore, in S1, the copper-zinc-tin-sulfur precursor film is obtained by depositing a precursor solution on a flexible substrate, and the precursor solution is Cu(CH3COO)2·H2O, SnCl2·2H2O, ZnCl2, and CH4N2S dissolved in N,N-dimethylformamide (DMF) in sequence, and the metal molar ratios are Cu / (Zn+Sn)=0.6~0.75, Zn / Sn=1.0~1.5, and Cu+Sn+Zn / S=1~0.9, respectively.
[0013] Furthermore, in S2, the inversion refers to a placement in which the copper-zinc-tin-sulfur precursor film faces downward and the flexible substrate faces upward.
[0014] Furthermore, in S2, the temperature of the selenization annealing is 540-560°C.
[0015] Furthermore, in S2, the selenization annealing time is 12 to 15 minutes.
[0016] Furthermore, in S2, the operation of selenization annealing includes: placing selenium particles in a graphite box, mounting the Mo glass on the graphite box, and placing the copper-zinc-tin-sulfur precursor film obtained in S1 upside down on the Mo glass, and heating it in a nitrogen atmosphere.
[0017] Furthermore, in S3, a buffer layer CdS film is first deposited on the copper-zinc-tin-sulfur-selenium film, then an intrinsic zinc oxide layer is deposited, and then an aluminum-doped zinc oxide layer is deposited, and finally a silver electrode is deposited to obtain a flexible copper-zinc-tin-sulfur-selenium thin film solar cell.
[0018] Furthermore, the thickness of the buffer layer CdS film is 30-50 nanometers, the thickness of the intrinsic zinc oxide layer is 40-60 nanometers, the thickness of the aluminum-doped zinc oxide layer is 200-300 nanometers, and the thickness of the silver electrode is 0.5-1.5 micrometers.
[0019] The beneficial effects of the present invention are:
[0020] The present invention places a copper-zinc-tin-sulfur precursor film on a soda-lime glass coated with a Mo layer for annealing, thereby not only providing a simple and effective means for alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery, but also realizing the regulated doping of alkali metals in the copper-zinc-tin-sulfur-selenium film, thereby avoiding damage to the flexible device caused by excessive alkali metal doping. Ultimately, the photoelectric conversion efficiency of the flexible copper-zinc-tin-sulfur-selenium device is significantly improved by autonomously adjusting the alkali metal content in the copper-zinc-tin-sulfur-selenium film, thereby effectively improving the performance of the flexible CZTSSe solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope of the present invention.
[0022] Figure 1 This is the XPS characterization diagram of CZTSSe-1 and CZTSSe-2 samples in Example 1.
[0023] Figure 2 Schematic diagram of the average battery parameters of the devices Cell-1 and Cell-2 in Example 2.
[0024] Figure 3 This is a JV curve diagram of the device at different selenization temperatures in Example 3. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0026] The present invention provides a method for regulating alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery, comprising the following steps:
[0027] S1: Deposition of CuZnSnS precursor thin films on flexible substrates.
[0028] In some preferred embodiments of the present invention, the flexible substrate includes but is not limited to a metal molybdenum foil substrate.
[0029] In some preferred embodiments of the present invention, S1 specifically dissolves Cu(CH3COO)2·H2O, SnCl2·2H2O, ZnCl2, and CH4N2S in N,N-dimethylformamide (DMF) in sequence to prepare a precursor solution; the metal molar ratios in the precursor solution are Cu / (Zn+Sn)=0.6~0.75, Zn / Sn=1.0~1.5, and Cu+Sn+Zn / S=1~0.9; the metal ion concentration in the precursor solution is 2.0M; and then the precursor solution is deposited on a flexible substrate by spin coating or the like.
[0030] S2: Inverting the copper-zinc-tin-sulfur precursor film deposited on the flexible substrate on Mo glass for selenization annealing, where the Mo glass is soda-lime glass coated with a Mo layer; the selenization annealing can achieve the diffusion of alkali metals in the soda-lime glass and doping them into the copper-zinc-tin-sulfur-selenium film, where the alkali metals include sodium and potassium.
[0031] Here, inverted refers to a placement method in which the copper-zinc-tin-sulfur precursor film faces downward (ie, the copper-zinc-tin-sulfur precursor film faces the Mo layer) and the flexible substrate faces upward.
[0032] In some preferred embodiments of the present invention, the temperature of the selenization annealing is 540-560°C.
[0033] In some preferred embodiments of the present invention, the time of selenization annealing is 12 to 15 minutes.
[0034] In some preferred embodiments of the present invention, the operation of selenization annealing includes: placing selenium particles in a graphite box, installing Mo glass on the graphite box, and placing the copper-zinc-tin-sulfur precursor film obtained in S1 upside down on the Mo glass, and then heating in a nitrogen atmosphere to perform a selenization annealing process.
[0035] S3: A flexible copper-zinc-tin-sulfur-selenium cell is prepared based on a copper-zinc-tin-sulfur-selenium film doped with alkali metals: the copper-zinc-tin-sulfur-selenium film (including a flexible substrate) after selenization annealing is taken out, a buffer layer CdS film is first deposited on the copper-zinc-tin-sulfur-selenium film, then an intrinsic zinc oxide layer is deposited, and then an aluminum-doped zinc oxide layer is deposited, and finally a silver electrode is deposited to obtain a flexible copper-zinc-tin-sulfur-selenium thin film solar cell.
[0036] In some preferred embodiments of the present invention, the thickness of the buffer layer CdS film is 30-50 nanometers, the thickness of the intrinsic zinc oxide layer is 40-60 nanometers, the thickness of the aluminum-doped zinc oxide layer is 200-300 nanometers, and the thickness of the silver electrode is 0.5-1.5 micrometers.
[0037] Example 1
[0038] The copper-zinc-tin-sulfur-selenide thin films were prepared according to the following steps, and the effects of different preparation methods on alkali metal doping were investigated:
[0039] (1) Cu(CH3COO)2·H2O, SnCl2·2H2O, ZnCl2, and CH4N2S are dissolved in N,N-dimethylformamide (DMF) in sequence to prepare a precursor solution; the metal molar ratios in the precursor solution are Cu / (Zn+Sn)=0.7, Zn / Sn=1.0, and Cu+Sn+Zn / S=1; the metal ion concentration in the precursor solution is 2.0 M; then the precursor solution is spin-coated on a flexible substrate to obtain a copper-zinc-tin-sulfur precursor film deposited on the flexible substrate.
[0040] (2) Selenium particles were placed in a graphite box, and the copper-zinc-tin-sulfur precursor film deposited on the flexible substrate was placed upside down on the bare soda-lime glass and Mo glass, respectively, and the selenization annealing process was carried out in a nitrogen atmosphere. The selenization temperature was 560°C and the selenization time was 15 minutes. The copper-zinc-tin-sulfur-selenium films obtained on the soda-lime glass and Mo glass were named CZTSSe-1 and CZTSSe-2, respectively. For comparison, the sample that was selenized annealed without any support and with the film surface facing up was named CZTSSe-control.
[0041] XPS characterization was performed on the above three samples to detect the surface alkali metal element Na, such as Figure 1As shown. Among them, the Na peak was not detected in the sample CZTSSe-control, while the Na peak was detected in the samples CZTSSe-1 and CZTSSe-2, indicating that the method of the present invention achieves Na doping of the copper-zinc-tin-sulfur-selenide film; and the Na peak of the sample CZTSSe-1 is stronger than that of the sample CZTSSe-2. In addition, Table 1 shows the surface Na / Cu+Zn+Sn content detected by XPS. The Na / Cu+Zn+Sn of the sample CZTSSe-1 is higher than that of the sample CZTSSe-2, which can indicate that the Na content in the sample CZTSSe-1 is higher than that in the sample CZTSSe-2, that is, the existence of the Mo layer can regulate the diffusion process of Na during the selenization process, thereby appropriately reducing the Na content in the copper-zinc-tin-sulfur-selenide film.
[0042] Table 1. Na / Cu+Zn+Sn element contents obtained by XPS
[0043]
[0044] Example 2
[0045] The flexible copper-zinc-tin-sulfur-selenium thin film solar cells were prepared according to the following steps, and the effects of different preparation methods on device performance were investigated:
[0046] (1) Cu(CH3COO)2·H2O, SnCl2·2H2O, ZnCl2, and CH4N2S are dissolved in N,N-dimethylformamide (DMF) in sequence to prepare a precursor solution; the metal molar ratios in the precursor solution are Cu / (Zn+Sn)=0.7, Zn / Sn=1.0, and Cu+Sn+Zn / S=1; the metal ion concentration in the precursor solution is 2.0 M; then the precursor solution is spin-coated on a flexible substrate to obtain a copper-zinc-tin-sulfur precursor film deposited on the flexible substrate.
[0047] (2) Selenium particles were placed in a graphite box, and the copper-zinc-tin-sulfur precursor film deposited on the flexible substrate was placed upside down on the exposed soda-lime glass and Mo glass, respectively, and a selenization annealing process was performed in a nitrogen atmosphere. The selenization temperature was 560°C and the selenization time was 15 minutes. The copper-zinc-tin-sulfur-selenium films obtained on the soda-lime glass and Mo glass were named CZTSSe-1 and CZTSSe-2, respectively.
[0048] (3) On the above two copper-zinc-tin-sulfur-selenide thin films, a buffer layer CdS with a thickness of 50 nanometers was deposited, and then an intrinsic zinc oxide layer with a thickness of 20 nanometers was deposited, and then an aluminum-doped zinc oxide layer with a thickness of 300 nanometers was deposited, and finally a silver electrode with a thickness of 0.5 micrometers was deposited to obtain a flexible copper-zinc-tin-sulfur-selenide thin film solar cell. The flexible copper-zinc-tin-sulfur-selenide thin film solar cells prepared based on CZTSSe-1 and CZTSSe-2 copper-zinc-tin-sulfur-selenide thin films are named Cell-1 and Cell-2, respectively. The average parameters of the two devices are shown in the figure. Figure 2 As shown, from Figure 2 It can be seen that compared with Cell-1, the performance of Cell-2 has been significantly improved, the average efficiency of the device has been significantly improved, and the short-circuit current, open-circuit voltage and fill factor have all been improved.
[0049] Example 3
[0050] The flexible copper-zinc-tin-sulfur-selenium thin film solar cells were prepared according to the following steps, and the effect of preparation at different selenization temperatures on device performance was investigated:
[0051] (1) Cu(CH3COO)2·H2O, SnCl2·2H2O, ZnCl2, and CH4N2S are dissolved in N,N-dimethylformamide (DMF) in sequence to prepare a precursor solution; the metal molar ratios in the precursor solution are Cu / (Zn+Sn)=0.7, Zn / Sn=1.0, and Cu+Sn+Zn / S=1; the metal ion concentration in the precursor solution is 2.0 M; then the precursor solution is spin-coated on a flexible substrate to obtain a copper-zinc-tin-sulfur precursor film deposited on the flexible substrate.
[0052] (2) Selenium particles were placed in a graphite box, and the copper-zinc-tin-sulfur precursor film deposited on the flexible substrate was placed upside down on the Mo glass, and a selenization annealing process was performed in a nitrogen atmosphere. The selenization temperatures were 530°C, 540°C, 550°C, 560°C, and 570°C, and the selenization time was 15 minutes.
[0053] (3) On the five copper-zinc-tin-sulfur-selenium thin films obtained in step (2), a buffer layer CdS with a thickness of 50 nanometers was deposited, followed by an intrinsic zinc oxide layer with a thickness of 20 nanometers, and then an aluminum-doped zinc oxide layer with a thickness of 300 nanometers. Finally, a silver electrode with a thickness of 0.5 micrometers was deposited to obtain the JV curve of the flexible copper-zinc-tin-sulfur-selenium thin film solar cell device as shown below: Figure 3 Table 2 shows the detailed information of device parameters. Figure 3 As can be seen from Table 2, the selenization temperature is suitable for 540 ~ 560 ℃, and the device performance is best when the selenization temperature is 560 ℃.
[0054] Table 2. Device parameters at different selenization temperatures
[0055]
[0056]
[0057] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.
Claims
1. A method for regulating alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery, characterized in that: The steps include: S1: Deposition of copper-zinc-tin-sulfur precursor thin films on flexible substrates; S2: placing the copper-zinc-tin-sulfur precursor film deposited on the flexible substrate upside down on Mo glass for selenization annealing, wherein the Mo glass is soda-lime glass coated with a Mo layer; the selenization annealing can achieve diffusion of alkali metals in the soda-lime glass and doping them into the copper-zinc-tin-sulfur-selenium film, wherein the alkali metals include sodium and potassium elements; S3: A flexible copper-zinc-tin-sulfur-selenium battery is prepared based on a copper-zinc-tin-sulfur-selenium film doped with alkali metals.
2. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 1, characterized in that: In S1, the copper-zinc-tin-sulfur precursor film is obtained by depositing a precursor solution on a flexible substrate. The precursor solution is prepared by dissolving Cu(CH3COO)2·H2O, SnCl2·2H2O, ZnCl2, and CH4N2S in N,N-dimethylformamide in sequence, and the metal molar ratios are Cu / (Zn+Sn)=0.6~0.75, Zn / Sn=1.0~1.5, and Cu+Sn+Zn / S=1~0.9, respectively.
3. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 1, characterized in that: In S2, the inversion refers to a placement in which the copper-zinc-tin-sulfur precursor film faces downward and the flexible substrate faces upward.
4. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 1, characterized in that: In S2, the temperature of the selenization annealing is 540-560°C.
5. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 1, characterized in that: In S2, the selenization annealing time is 12 to 15 minutes.
6. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 1, characterized in that: In S2, the selenization annealing operation includes: placing selenium particles in a graphite box, mounting the Mo glass on the graphite box, and placing the copper-zinc-tin-sulfur precursor film obtained in S1 upside down on the Mo glass, and heating it in a nitrogen atmosphere.
7. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 1, characterized in that: In S3, a buffer layer CdS film is first deposited on the copper-zinc-tin-sulfur-selenide film, then an intrinsic zinc oxide layer is deposited, then an aluminum-doped zinc oxide layer is deposited, and finally a silver electrode is deposited to obtain a flexible copper-zinc-tin-sulfur-selenide thin film solar cell.
8. The method for controlling alkali metal doping in a flexible copper-zinc-tin-sulfur-selenium battery according to claim 7, characterized in that: The thickness of the buffer layer CdS film is 30-50 nanometers, the thickness of the intrinsic zinc oxide layer is 40-60 nanometers, the thickness of the aluminum-doped zinc oxide layer is 200-300 nanometers, and the thickness of the silver electrode is 0.5-1.5 micrometers.
